A política de precarização do trabalho do agente escolar na educação infantil do município de Cascavel (PR) - Amado, Bruno Ribeiro (2022)
In this master's thesis, we aimed to understand how the creation of the position of Support Agent, materialized by public policies that regulate the care in Early Childhood Education, can contribute to the precariousness of the work of the Early Childhood Education teacher in the Municipal Public Education Network of Cascavel (PR). This proposal is justified by the fact that this professional works directly in Early Childhood Education in this city. Methodologically, bibliographic research was developed in primary and secondary sources and field research with support agents of that city. In the first chapter, we sought to understand the history of the institutionalization of Early Childhood Education in Brazil and in Cascavel (PR), the public policies that regulate this stage of Basic Education and the specificity of teaching in Early Childhood Education, based on laws and authors such as Kuhlmann Jr. (2000), Arce (2001), Paschoal and Machado (2009), Pagnoncelli (2015), Pinheiro (2017) Filipim, Rossi and Rodrigues (2017) and others. In the second chapter, the scope was to analyze the legislation that regulates labor relations in Brazil and the function of support agent, resorting, thus, to the laws and notices of competition that effected the hiring of this professional. Authors such as Braga (2012), Marini (2013), Antunes (2014a, 2014b), Raposo (2017), Deitos (2019) and others were essential to the reflection. As a result, it was possible to understand that, in the process of restructuring the world economy in the 1990s, Brazil integrated into the globalized economy, which is based on the exploitation of cheap and precarious labor, with the characteristic of a framework of structural precariousness of labor. Moreover, it was found that the position of support agent is configured as a contradictory element in the history of early childhood education, since the 1988 Federal Constitution recognizes this as the first stage of basic education, assigning pedagogical character, which is also reinforced by the Curriculum for the Municipal Public Education Network of Cascavel (PR), which considers early childhood education as a period of socialization of scientific, philosophical and artistic knowledge, which should be mediated by the teacher and not by a professional without training in the area, as is the case of the support agent.